Eliciting and integrating expert knowledge to assess the viability of the critically endangered golden sun‐moth Synemon plana. (6th September 2016) - Mata, Luis; Garrard, Georgia E.; Kutt, Alex S.; Wintle, Bonnie C.; Chee, Yung En; Backstrom, Anna; Bainbridge, Brian; Urlus, Jake; Brown, Geoff W.; Tolsma, Arn D.; Yen, Alan L.; New, Timothy R.; et al.
Abstract: The critically endangered golden sun‐moth Synemon plana occurs in urban fringe areas of southeastern Australia that are currently experiencing rapid and extensive development. The urban fringe is a complex and uncertain environment in which to manage threatened species with the intersection of fragmented natural habitats, built environments and human populations generating novel, poorly understood interactions. In this context, management frameworks must incorporate ecological processes as well as social considerations. Here, we explore how biodiversity sensitive urban design might improve the fate of the golden sun‐moth, and threatened species generally, in urban fringe environments. We: (i) developed an expert‐informed Bayesian Belief Network model that synthesizes the current understanding of key determinants of golden sun‐moth population viability at sites experiencing urbanizing pressure; (ii) quantified the nature and strength of cause‐effect relationships between these factors using expert knowledge; and (iii) used the model to assess expectations of moth population viability in response to different combinations of management actions. We predict that adult survival, bare ground cover and cover of resource plants are the most important variables affecting the viability of golden sun‐moth populations. We also demonstrate the potential for biodiversity sensitive urban design as a complementary measure to conventional management for this species. Our findings highlight how expert knowledge may be a valuable component of conservation management, especially in addressing uncertainty around conservation decisions when empirical data are lacking, and how structured expert judgements become critical in supporting decisions that may help ameliorate extinction risks faced by threatened species in urban environments.